Synthetic biology for Taxol biosynthesis and sustainable production - Xie, Linfeng; Gao, Jiaoqi; Zhou, Yongjin J. (Trends in biotechnology (Regular ed.), 2024)
Incomplete understanding of the biosynthetic pathway of the anticancer compound Taxol hinders its production by metabolic engineering. Recent reports by Jiang et al. and other groups now describe the missing steps in Taxol biosynthesis, notably including oxetane ring formation. These findings will promote the sustainable production of Taxol through synthetic biology. Incomplete understanding of the biosynthetic pathway of the anticancer compound Taxol hinders its production by metabolic engineering. Recent reports by Jiang et al. and other groups now describe the missing steps in Taxol biosynthesis, notably including oxetane ring formation. These findings will promote the sustainable production of Taxol through synthetic biology.